2021
DOI: 10.1371/journal.pone.0253913
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Multidimensional Assessment of Interoceptive Awareness (MAIA-2) questionnaire in hospitalized patients with major depressive disorder

Abstract: Objectives Interoception refers to the sensation, interpretation, and integration of internal somatic signals. Abnormalities in self-reported interoception are prevalent features of major depressive disorder (MDD) and may affect treatment outcomes. In the present study, we investigated the psychometric properties of the revised eight-dimensional and 37-item Multidimensional Assessment of Interoceptive Awareness questionnaire (the MAIA-2) in a severely depressed sample, after translating two updated scales (Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 119 publications
3
37
0
1
Order By: Relevance
“…The internal reliabilities of the subscales were as follows: Noticing (0.76), Not-Distracting (0.87), Not-Worrying (0.56), Attention Regulation (0.86), Emotional Awareness (0.85), Self-Regulation (0.85), Body Listening (0.85), and Body Trust (0.87). Notably, the low internal consistency of the Not-Worrying subscale is in keeping with other studies that have found similarly low reliabilities for this subscale [29,30].…”
Section: Methodssupporting
confidence: 88%
“…The internal reliabilities of the subscales were as follows: Noticing (0.76), Not-Distracting (0.87), Not-Worrying (0.56), Attention Regulation (0.86), Emotional Awareness (0.85), Self-Regulation (0.85), Body Listening (0.85), and Body Trust (0.87). Notably, the low internal consistency of the Not-Worrying subscale is in keeping with other studies that have found similarly low reliabilities for this subscale [29,30].…”
Section: Methodssupporting
confidence: 88%
“…The internal consistency, as measured by Cronbach's alpha, was below 0.70 for the subscales "Noticing", "Not-Distracting", and "Not-Worrying" and was confirmed in some subsequent studies. The other subscales ranged from 0.79 to 0.87 [6,37,[42][43][44][45][46][47][48][49][50][51][52][53][54]. The confirmatory factor analysis confirmed the multidimensionality of the scale [6].…”
Section: Introductionmentioning
confidence: 78%
“…Importantly, neither of these studies incorporated sex or severity of co-occurring psychiatric symptoms into their analyses ( 53 , 56 ). These clinical factors are critical considerations in studies of interoceptive sensibility given evidence of divergent interoceptive sensibility between the sexes ( 65 , 91 ) and atypical interoceptive sensibility in depressive ( 92 , 93 ), anxiety ( 94 , 95 ), and obsessive-compulsive disorders ( 64 ). Among individuals with CTD, lifetime prevalence of depression, anxiety, and OCD is 30, 36, and 66%, respectively ( 57 ), highlighting the relevance of these conditions when researching interoception in CTD populations.…”
Section: Discussionmentioning
confidence: 99%